Daryl Wayne Flint's Psychopathic Disorder in Carla Norton's Hunted - Fa'iqoh, Nur Auliyana; Wahyono, Danu (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2023)
The study, entitled Daryl Wayne Flint's Psychopathic Disorder in Carla Norton's Hunted, studies the main character Daryl Wayne Flint who has various abnormal characteristics. The study aims to provide further information about psychopathic disorders. This research broadly explains the paradigm, causes, and effects of psychopathic disorder using a qualitative descriptive method combined with a psychological approach. The findings of Flint's symptoms are narcissistic, antisocial, aggressive sadism, and a strong paranoia orientation. The underlying cause for this disorder is started from childhood trauma and the environment that causes a lack of sympathy, negative internal states, and bad repetitive behavior. Flint also causes severe negative effects on his surroundings, including excessive sadistic aggression and long-term trauma for the survivors. Based on the findings above, Flint is a positive psychopathic disorder by showing a tendency for repetitive destructive behavior.